2013
DOI: 10.13064/ksss.2013.5.4.071
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Voice Analysis of Children with Cochlear Implant and with Normal Hearing

Abstract: The purpose of this study was to compare the acoustic voice outcomes of children with cochlear implant to those of children with normal hearing. Participants were 41 children using unilateral cochlear implant (18 males and 23 females), and children with normal hearing from the same age and sex. Mean age of implantation was approximately 3 years old, mean duration of implant use was 4 years in CI group. Acoustic analyses were performed using MDVP of CSL. Speech samples were 3 sustained vowels, /a, i, u/. 9 para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…Moreover, Lee et al [19] analyzed the speech acceptability of hearing-impaired adults and reported that the speech acceptability of them was more strongly correlated with supra-segmental factors than segmental factors, and consonant accuracy, intonation, resonance, and speech rate were major variables influencing speech acceptability. Previous studies [28,29] that analyzed the acoustic and phonetic characteristics of speech made by hearing impaired children with wearing CI showed that the pitch and quality related indices of children wearing CI were different from those of healthy hearing children. Hsu et al [30], who evaluated auditory senses, also showed that the speech characteristics of children wearing CI were different from those of healthy hearing children in terms of pitch, quality, and resonance.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Lee et al [19] analyzed the speech acceptability of hearing-impaired adults and reported that the speech acceptability of them was more strongly correlated with supra-segmental factors than segmental factors, and consonant accuracy, intonation, resonance, and speech rate were major variables influencing speech acceptability. Previous studies [28,29] that analyzed the acoustic and phonetic characteristics of speech made by hearing impaired children with wearing CI showed that the pitch and quality related indices of children wearing CI were different from those of healthy hearing children. Hsu et al [30], who evaluated auditory senses, also showed that the speech characteristics of children wearing CI were different from those of healthy hearing children in terms of pitch, quality, and resonance.…”
Section: Discussionmentioning
confidence: 97%
“…에서 정상 집단보다 낮게 나타났으며, 파열음 산출에서는 산출 기간이 길고 경음을 연음처럼 산출하는 특성이 나타났다 (Kim et al, 2014). 건청 아동과 보장구를 사용한 청각장애 아동 연 구에서도 청각적 피드백이 부족할수록 음성의 음도가 높고, 강 도가 크며 (Yoon, 2006), 청각장애 아동은 보장구의 착용 기간 이 길어질수록 음도와 강도가 건청 아동들과 유사한 음향학적 특성이 나타났다고 보고하였다 (Bae et al, 2014) (Bae et al, 2014;Waldstein, 1990). (Ferrand, 2014;Milbrath & Solmon, 2003) (Shim et al, 2016)…”
unclassified
“…들과 다른 특징을 보인다는 연구도 지속적으로 발표되고 있다 (Fang et al, 2014;Kang & Yoon, 2020;Wang et al, 2017;Yoon et al, 2013). 이러한 연구 결과들은 인공와우이식 아동이 호흡, 발 성, 조음의 순간적인 협응이 요구되는 파열음의 지각 및 산출에 서 어려움이 있다는 것을 시사한다.…”
unclassified